Karakteristik Komuter dan Moda Suroboyo Bus Electric Rute Purabaya-ITS di Surabaya - Erlangga Isnaini; Septiana Hariyani; Dadang Meru Utomo (Pusat riset dan Inovasi Nasional, 2026)
Urban mobility in Surabaya faces serious challenges due to the high ownership of private vehicles and the low use of public transportation. The Surabaya City Government launched Suroboyo Bus Electric in November 2024 as a sustainable transportation innovation on the Purabaya–ITS route. This study aims to analyze commuter preferences for the Suroboyo Bus Electric mode over private vehicles, by emphasizing functional factors (cost, travel time, comfort) and symbolic factors (status, identity, modern image). The research method used a quantitative descriptive approach with 400 respondents, primary data was obtained through questionnaires, while secondary data came from government documents and literature. The analysis was carried out through descriptive statistics, chi-square tests, and logistic regression. The results showed that the majority of respondents chose Suroboyo Bus Electric as the main mode (62%), with the dominance of young, middle-income users, and mostly women. Most of the respondents have one unit of private vehicle, but still use electric buses as a mode of complementing mobility. Travel destinations are dominated by social, economic, and educational activities, with an average travel time of 16–30 minutes. In terms of cost, more than half of the respondents spent Rp 5,000-Rp 10,000 per trip, indicating the affordability of fares. Symbolic factors also play an important role, where Suroboyo Bus Electric is perceived as a modern, clean, and sustainable city identity.